New Distributional Record of Eupterote Testacea (Walker, 1855) (Lepidoptera, Eupterotidae) From Sylhet Division, Bangladesh (Bangladesh Journal of Zoology, 2021)
Abstract not availableBangladesh J. Zool. 49(1): 169-173, 2021